Kritik Sosial dalam Lagu “Bayar Bayar Bayar” Karya Band Sukatani - Dede Fadilatunisa; Dwi Wahyu Candra Dewi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
The song "Bayar Bayar Bayar" by the band Sukatani describes a social critique of injustice in public services in Indonesia, especially those involving the police institution. Through simple yet meaningful repetitive lyrics, the song reflects the reality of people's lives who have to face additional costs to obtain public services that should be free or fair. In this analysis, the song is connected to Nancy Fraser's concept of social injustice, which shows the inequality in the distribution of social rights, as well as the instrumental theory of law which states that law is often a tool for certain interests. The aesthetic techniques used in the song, including repetition and hyperbole, strengthen the message of social criticism, making it a means of resistance to corrupt social structures. In the Indonesian social context, the song also serves as a reflection of society's distrust of public institutions and becomes a medium of expression that encourages collective awareness of broader issues of injustice.